IMPORTANCE OF COLORS AND THEIR IMPLEMENTATION - Mathew, Archana; Aijaz, Azra (International Journal of Research -GRANTHAALAYAH, 2014)
Science has long recognised that colour affects our behaviour and the way we feel. After all, it is the first thing we register and that we use to help assess the things around us, such as whether certain foods, such as blue ones, might be poisonous, for example. To understand these responses, we need to look at how colour works. Essentially, when the light reflected from coloured objects strikes the retinas in our eyes, the wavelengths are converted into electrical impulses. These pass into the part of the brain that rules our hormones and endocrine system, which are instrumental in regulating our moods. Unconsciously, then, our eyes and bodies constantly adapt to these stimuli, influencing our impulses and perceptions.